Faculty-librarian collaborative culture in the universities of Hong Kong, Singapore, Taiwan, and Thailand: A comparative study - Yu, Ti; Chen, Chao-chen; Khoo, Christopher; Butdisuwan, Sujin; Ma, Leo; Sacchanand, Chutima; Tuamsuk, Kulthida (Malaysian Journal of Library and Information Science, 2019)
This study considers that â€œcollaborative cultureâ€ is the basis for faculty members and librarians to work together in higher education institutions. The study therefore attempts to explore the collaboration between faculty members and librarians from the perspective of culture. It can not only provide an opportunity to elucidate the current development of the faculty-librarian collaboration in some parts of Southeast Asia such as Hong Kong, Singapore, Thailand, and Taiwan, but also compare the distinctions in the value of faculty-librarian collaborative culture. It also aims to describe and evaluate the perceptions/experiences toward the current development of faculty-librarian collaboration in universities in these different countries. Two online questionnaires, entitled â€œFaculty-librarian Collaboration Survey-Librarianâ€ and â€œFaculty-librarian Collaboration Survey-Facultyâ€, were designed and developed by the researchers to collect data. 480 valid responses were collected from December 2015 to May 2016. Seven key elements were investigated in this study that can represent the content and concept of faculty-librarian collaborative culture. They are: (1) Organizational collaborative environment; (2) Mutual benefit and responsibility in collaboration; (3) Collaborative commitment; (4) Collaborative leadership; (5) Mutual understanding and communication; (6) Mutual respect and trust; and (7) Collaborative relationship and interaction. It was concluded that the responding faculty members and librarians in different regions of Southeast Asia, including Hong Kong, Singapore, Thailand, and Taiwan exhibited distinctions in the value levels of faculty-librarian collaborative culture, as well as in the perceptions/experiences toward the current development of faculty-librarian collaboration. Finally, a number of implications and suggestions were proposed by the researchers for librarians and faculty members to develop faculty-librarian collaborations in Hong Kong, Singapore, Thailand, and Taiwan, respectively.